2018
DOI: 10.1089/lgbt.2017.0098
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to HIV Prevention Services for Transgender Youth

Abstract: Transgender youth may not discuss their GSM identity or sexual health with PCPs because they anticipate GSM stigma and fear being "outed" to parents. PCPs should receive transgender-inclusive training to adequately address youths' sexual health needs and privacy concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 45 publications
2
56
0
4
Order By: Relevance
“…When faced with experiences of constant discrimination and violence, TGD individuals feel exhausted, develop a concern about their safety, and may begin to anticipate rejection or avoid settings where they either have or could encounter marginalization (Puckett, Cleary, Rossman, Mustanski, & Newcomb, ; Rood et al, ). For instance, many TGD youth fear stigma from their medical providers (Fisher, Fried, Desmond, Macapagal, & Mustanski, ) and TGD individuals who encounter discrimination in health care settings may be more likely to avoid or delay seeking treatment (Glick et al, ). This prior research shows that discrimination has implications for many aspects of TGD people's lives.…”
Section: Discrimination and Psychological Distressmentioning
confidence: 99%
“…When faced with experiences of constant discrimination and violence, TGD individuals feel exhausted, develop a concern about their safety, and may begin to anticipate rejection or avoid settings where they either have or could encounter marginalization (Puckett, Cleary, Rossman, Mustanski, & Newcomb, ; Rood et al, ). For instance, many TGD youth fear stigma from their medical providers (Fisher, Fried, Desmond, Macapagal, & Mustanski, ) and TGD individuals who encounter discrimination in health care settings may be more likely to avoid or delay seeking treatment (Glick et al, ). This prior research shows that discrimination has implications for many aspects of TGD people's lives.…”
Section: Discrimination and Psychological Distressmentioning
confidence: 99%
“…Adults with nonbinary identities report difficulty accessing affirming health care, even in clinics designed to provide care for transgender patients . Among transgender and gender nonconforming youth, nonbinary youth are less likely to be out to their primary parent or guardian than transgender peers with binary identities . The few studies that have examined mental health among youth with nonbinary identities have shown high rates of attempted suicide, low mental health scores, and high rates of self‐harm .…”
Section: School Experiences For Tng Youthmentioning
confidence: 99%
“…Half (50%) of the participants identified as transgender women, 38% as cisgender men, and 12% as transgender men. Participant median age was 26 years (range [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…This setting allowed providers to address barriers to PrEP access that have been previously described, such as high cost and provider hesitation to discuss PrEP and/or gender identity. [16][17][18] Despite providing services in a setting specifically designed for LGBTQ youth, both retention and adherence were suboptimal. This is consistent with other studies of PrEP adherence among transgender women 19 and young men who have sex with men 5,6 in which a majority of participants did not have evidence of highly protective drug levels over time.…”
Section: Discussionmentioning
confidence: 99%